Mineralogy and microstructure of the Morasko meteorite crust. (1st December 2018) - Duczmal-Czernikiewicz, Agata; Michalska, Danuta
Abstract: This study examines the mineral composition, the diversity of chemical composition along the contact area between the Morasko meteorite fragments (classified as iron meteorite, IAB group), the meteorite crust and the surrounding sediments originating from the young glacial relief of the Morasko Reservoir (N part of Poznan, western Poland). It has been shown that the grains are dominated by quartz and feldspars, which are associated with a ferric or ferric-carbonate matrix. The chemical composition of the matrix varies from high iron (over 98% by weight) and nickel (2–3% by weight) content in the meteorite contact area, to low iron content and nickel deficiency, with an oxygen increase in the outer zone about 2 mm from the meteorite. The microstructure of the contact zone is characterized by uneven cracks and deformations of the skeleton grains as well as sediment matrix. This paper for the first time shows the Morasko meteorite structure in reflected light, giving new perspectives in meteorite outer zone characteristic. Highlights: Diversity of contact area between the Morasko meteorite fragment (IAB) and its outer zone were examined. The outer zone bears traces of surrounding sediment. Successful application of reflected light in Morasko meteorite structure observations and characteristic. Chemical composition of the contact zone reveals oxidation processes associated with weathering. The contact zone underwent weathering processes in terrestrial conditionsresulted in hematite and goethite formation..